Determinants of the interindividual variability in serum cytidine deaminase activity of patients with solid tumours. Issue 6 (30th January 2019) - Cohen, R.; Preta, L. H.; Joste, V.; Curis, E.; Huillard, O.; Jouinot, A.; Narjoz, C.; Thomas‐Schoemann, A.; Bellesoeur, A.; Tiako Meyo, M.; Quilichini, J.; Desaulle, D.; et al.
Abstract : Aims: Cytidine deaminase (CDA) activity in cancer patients' serum has been proposed as a predictive biomarker for efficacy and toxicity of nucleoside analogues. However, discrepant results about its predictive value have been reported due to the high interindividual variability in CDA activity. This study aimed at identifying determinants of this interindividual variability. Methods: From December 2014 to November 2015, 183 patients were prospectively included. Serum CDA activity, biological and clinical characteristics as well as five common single nucleotide polymorphisms (SNPs) in the CDA gene (c.‐451C > T, c.‐92A > G, c.‐33_‐31delC, c.79A > C, c.435 T > C) were analysed. Associations between clinical characteristics, pharmacogenetic variants and CDA activity were univariately tested. P < 0.1‐candidate variables were analysed through a multivariate analysis. The association between CDA activity and toxicity was assessed for the 56 gemcitabine‐treated patients. Intraindividual variability in CDA activity was explored in six pancreatic cancer patients treated with gemcitabine. Results: Median CDA activity was 3.97 U mg –1 (range 1.53–15.49 U mg –1 ). A univariate analysis showed that CDA activity was statistically associated with Eastern Cooperative Oncology Group performance status, mild or severe malnutrition, inflammatory syndrome, leucocyte count, neutrophil count, albumin, C‐reactive protein and ‐c.‐33_‐31delC single nucleotide polymorphism. A multivariate analysis identified that only neutrophil count ( P < 0.0001) and severe malnutrition ( P = 0.0278) were independently associated with CDA activity. Low CDA activity (<2 U mg –1 ) was not statistically associated with severe gemcitabine‐related toxicities ( P = 0.16). A decrease in CDA activity was observed during the longitudinal follow‐up of six pancreatic cancer patients treated with gemcitabine ( P = 0.03). Conclusions: These results suggest that neutrophil count and malnutrition should be considered for the interpretation of pretherapeutic CDA activity.